2016
DOI: 10.1111/ajt.13497
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Polymorphism in the CD59 Complement Regulatory Protein Gene in Donor Lungs Correlates With a Higher Risk for Chronic Rejection After Lung Transplantation

Abstract: Complement activation leads primarily to membrane attack complex formation and subsequent target cell lysis. Protection against self-damage is regulated by complement regulatory proteins, including CD46, CD55, and CD59. Within their promoter regions, singlenucleotide polymorphisms (SNPs) are present that could influence transcription. We analyzed these SNPs and investigated their influence on protein expression levels. A single SNP configuration in the promoter region of CD59 was found correlating with lower C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…Functional experiments indicated that lung endothelial cells and monocytes derived from lung donors with this SNP configuration showed lower CD59 expression and were more susceptible to complement‐mediated cell lysis . None of the polymorphisms within the CD46 and CD55 promoters correlated with incidence of BOS, nor did they correlate with expression levels and susceptibility to complement‐mediated cell lysis . We hypothesize that recipients of kidneys with this CD59 promoter SNP configuration may also be more prone to antibody‐mediated rejection and impaired graft survival.…”
Section: Potential Other Relevant Functional Complement Polymorphismsmentioning
confidence: 87%
See 1 more Smart Citation
“…Functional experiments indicated that lung endothelial cells and monocytes derived from lung donors with this SNP configuration showed lower CD59 expression and were more susceptible to complement‐mediated cell lysis . None of the polymorphisms within the CD46 and CD55 promoters correlated with incidence of BOS, nor did they correlate with expression levels and susceptibility to complement‐mediated cell lysis . We hypothesize that recipients of kidneys with this CD59 promoter SNP configuration may also be more prone to antibody‐mediated rejection and impaired graft survival.…”
Section: Potential Other Relevant Functional Complement Polymorphismsmentioning
confidence: 87%
“…Finally, in lung transplantation it was shown that a SNP in the promoter region of CD59 (rs147788946) in lung donors was associated with an increased risk for bronchiolitis obliterans syndrome (BOS) . Functional experiments indicated that lung endothelial cells and monocytes derived from lung donors with this SNP configuration showed lower CD59 expression and were more susceptible to complement‐mediated cell lysis .…”
Section: Potential Other Relevant Functional Complement Polymorphismsmentioning
confidence: 99%
“…CD59 inhibits formation of the membrane attack complex by preventing binding of C9 to C5b to C8 complexes. A SNP in the CD59 promotor region (rs147788946) of the donor was associated with higher risk for chronic rejection after lung transplantation . ADCC can be mediated by natural killer cells and to some extent monocytes and neutrophils.…”
Section: Effector Mechanisms Of Hla and Non‐hla Antibodiesmentioning
confidence: 99%
“…158 Graft-reactive antibodies induce the activation of the complement system and the degradation of lung tissues. Polymorphism in the complement regulatory protein CD59 has then been associated with the development of BOS, 159 suggesting that harnessing complement activation may control CLAD development. Complement activation has been largely investigated as a potential marker for humoral rejection, via the immunostaining of the complement component 4 (C4d).…”
Section: Humoral Immunitymentioning
confidence: 99%